Evaluation of Fly Ash Geopolymer on Bitumen Mixtures Against Moisture Damage - Ahmad Suhaimi , Nursyahirah; Aman, Mohamad Yusri (Recent Trends in Civil Engineering and Built Environment, 2023)
Presence of water in asphalt pavement may lead to adhesive failure at binder-aggregate interface and cohesive failures within the binder-filler mastic. The continuing action of moisture induced weakening and traffic load induced mechanical damaged can cause a progressive dislodgement of the aggregate, weakening of the aggregate-mastic bond and known as stripping of the pavement surface. This research presents the effects of newly additive material as anti-stripping known as fly ash geopolymer on asphalt mixtures. In this study, the asphalt mixtures incorporating fly ash geopolymer with 0%, 3%, 5%, 7%, 9% and 11% by mass of total mixture. Conventional bitumen 80/100 penetration grade was used as the base binder. The compacted specimen was conditioned for wet and dry condition and assessed the moisture sensitive according to the AASHTO T283. The result shows that the addition of 9% fly ash geopolymer in asphalt mixture conditioned for wet and dry condition indicates the highest of tensile strength at 1346.9 kPa and 1628.7 kPa, respectively. In contrast the specimens containing 11% fly ash geopolymer show a better resistance to moisture damage as 85% and comply to the standard specification. This due to the highest of wet ITS value compared to the dry specimen. From the result, conclusion can be made that the asphalt mixture prepared with various fly ash geopolymer percentage are compliance with the standard specification which is more than 80%. The specimens prepared with various fly ash geopolymer shows a good potential to the resistance moisture damage. The increasing of ITSR value produce a better the performance of the bitumen mixture with a greater withstands to moisture damage